2018
DOI: 10.1186/s12711-018-0374-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection models for directional dominance: an example for litter size in pigs

Abstract: BackgroundThe quantitative genetics theory argues that inbreeding depression and heterosis are founded on the existence of directional dominance. However, most procedures for genomic selection that have included dominance effects assumed prior symmetrical distributions. To address this, two alternatives can be considered: (1) assume the mean of dominance effects different from zero, and (2) use skewed distributions for the regularization of dominance effects. The aim of this study was to compare these approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 45 publications
(67 reference statements)
6
72
1
Order By: Relevance
“…Retinto (0.41 vs. 0.37 piglets 2 ) varieties evidenced the same pattern, although 95CI overlapped in both cases. It is important to highlight that several authors already suggested the relevance of non-additive sources of variation for fertility-related traits in domestic species (Fuerst and Sölkner, 1994;Nagy et al, 2013;Varona et al, 2018) Casellas (2018). This may lead to the underestimation of IDL effects, the same way major genes may bias predicted breeding values if not properly accounted for in the model (Legarra and Vitezica, 2015).…”
Section: Variance Componentsmentioning
confidence: 99%
“…Retinto (0.41 vs. 0.37 piglets 2 ) varieties evidenced the same pattern, although 95CI overlapped in both cases. It is important to highlight that several authors already suggested the relevance of non-additive sources of variation for fertility-related traits in domestic species (Fuerst and Sölkner, 1994;Nagy et al, 2013;Varona et al, 2018) Casellas (2018). This may lead to the underestimation of IDL effects, the same way major genes may bias predicted breeding values if not properly accounted for in the model (Legarra and Vitezica, 2015).…”
Section: Variance Componentsmentioning
confidence: 99%
“…The selection of one desirable allele over the rest normally implies the simultaneous selection and frequency increase of epistatically linked alleles, which in turn may not have a favorable effect on milk production traits and their components [ 10 ]. The approaches that are regularly followed to perform association analyses [ 11 ] normally overlook this genetic epistatic effects change during lactation [ 12 ], which renders the study of genetic association inefficient.…”
Section: Introductionmentioning
confidence: 99%
“…The high reproductive performance of a sow remains an important economic aspect of pig breeding (Dekkers, Mathur, & Knol, ; Rutherford et al, ; Spötter & Distl, ). Despite long‐term selection and high genetic gains achieved already for litter size in pigs, there are no signs of decline in genetic variation and heritability of this trait (Nielsen, Su, Lund, & Madsen, ; Putz, Tiezzi, Maltecca, Gray, & Knauer, ; Trenhaile, Petersen, Kachman, Johnson, & Ciobanu, ; Varona, Legarra, Herring, & Vitezica, ; Zhang et al, ). Still large variation in litter size between sows exists (Freyer, ; Sell‐Kubiak, Wang, Knol, & Mulder, ).…”
Section: Introductionmentioning
confidence: 99%